Exploring Connections Between People, Places and Food in Three Nova Scotia Farmers’ Markets - Lowitt, Kristen (Cuizine)

(untitled) (McGill University Library, 2009)
AbstractThis study explores connections between people, places and food in three Nova Scotia farmers’ markets through a series of qualitative interviews with consumers and producers. It introduces readers to the concept of “social embeddedness” as a means of understanding the social ties and reciprocal relationships that form in market environments, and deconstructs notions of “local” and “quality” food by exploring distinct understandings of these terms from the perspectives of producers and consumers.